Islamic resurgence and religiosity among the Malay middle and low income classes in Selangor and Kuala Lumpur, 1977-2014 / Mashitah Sulaiman - Mashitah , Sulaiman (2016)
This study analyses the phenomenon of Islamic Resurgence and its impact on the urban Malay Muslim middle and low income classes’ religiosity in Selangor and Kuala Lumpur, between 1977 to 2014. The period of the study began in 1977 for the reason that the initial official cooperation between the independent voluntary da’wah organisations, namely Muslim Youth Movement of Malaysia (ABIM) and World Association of Muslim Youth (WAMY); and the government agencies specifically, Islamic Centre and Foundation of Islamic Da’wah Malaysia (YADIM) started during the organisation of the Asian Muslim Youth Seminar on Da’wah in 1977, which then contributed to the great launching of Malaysian Da’wah Month in 1978. The year of 2014 was selected to end this study in conjunction with the great inauguration of the National Da’wah Program which ended with the National Da’wah Award in March 2015. The Exploratory Sequential Mixed Methods Design which combined the qualitative and quantitative methods were used for this multidisciplinary historical, Islamic studies and sociological research. Archives, official documents and records were analysed through content analysis using thematic and chronological approaches. Semi-structured interviews were conducted with six experts, 19 leaders of Islamic organisations and political parties, and 17 representatives of the Malay middle income and eight informants of the low income classes. 734 set of questionnaires was gathered using a combination of stratified, random and cluster samplings with the ratio of 2:4:4 respectively for the upper-middle income, the middle-middle income and the low income classes. Questionnaires were distributed randomly at Kuala Lumpur and in the nine districts of Selangor. Five clusters are government sector, Islamic NGO organisations, political party, factory and agricultural sectors and the public at large. Islamic Resurgence in Selangor and Kuala Lumpur was deeply facilitated by domestic factors and triggered by international circumstances in the Muslim world and counterparts. The dynamics of Islam in Malaysia, especially in the urban areas of Selangor and Kuala Lumpur continues to be a strong element to determine the Malay Muslim identity. Pragmatic and responsive roles of the government, the opposition Islamic party, the Islamic NGOs, the printed and electronic media accelerate the widespread of Islam in the public spheres. The study showed significant differences between the Malay low income and two groups of middle income classes, namely the uppermiddle and the middle-middle income in Islamic thoughts, practices and life styles. Economic status and household income are not the only indicators or determinant factors which help to increase a Muslim’s level in Islamic thoughts, practices and life styles. Islamic religiosity can also be contributed by self-awareness or responsibility, belief in the Islamic perfect way of life, personal attachment with Islamic da’wah organisations and institutions, family background and support, supportive public spheres, the role of government agencies, NGOs and Islamic political parties and mass media. Islamic Resurgence positively impacts the Malays at individual, social and international level in Selangor and Kuala Lumpur. The negative response of the Islamic Resurgence is traced through the involvement of a minority group of Malays in radical and terrorist activities.